Gastrointestinal Lymphorrhea Diagnosed by Exercise Lymphoscintigraphy. (December 2016) - Barić, Ana; Marković, Vinko; Arapović, Adela; Prgomet, Sandra; Saraga, Marijan
Abstract : Abstract: Lymphoscintigraphy is not considered as a first line diagnostic procedure in abdominal or thoracic lymphorrhea of various origin. We report a patient with lymphangiectasia in whom posttraumatic lymphorrhea was diagnosed by lymphoscintigraphy only after third attempt when we applied pushups exercise with the aim to raise venous pressure and thus provoke lymph backflow in ductus thoracicus and enteric lymphytics. Lymphorrhea was clearly visible in colon ascendens and colon transversum on 9h planar scintigram. We propose exercise lymphoscintigraphy with exercise tailored to individual patient's possibility before each lymphoscintigram to enhance lymphorrhea detection in patients with suspected lymph leakage.